Incidence and Variables Predictive of Pressure Injuries in Patients Undergoing Ventricular Assist Device and Total Artificial Heart Surgeries: An 8-Year Retrospective Cohort Study. (December 2020) - Brindle, Tod
ABSTRACT: OBJECTIVE: To investigate the incidence and risk factors of pressure injury (PI) development after ventricular assist device (VAD) or total artificial heart (TAH) surgery. METHODS: The investigator reviewed all VAD-TAH surgeries performed between 2010 and 2018 in a large academic health system. The PIs were reported by case incidence, patient incidence, and incidence density for each of the respective 1, 000 patient days during the study period. Statistics on four different VAD-TAH devices were assessed; variables significant in bivariate analysis were entered into a stepwise logistic regression model to identify significant predictors of PI. RESULTS: The sample included 292 independent VAD-TAH surgeries among 265 patients. Thirty-two patients developed 45 PIs. The PI incidence was 11% (32/292), with a PI incidence per patient of 12% (32/265). Incidence density was 10 per 1, 000 patient days (1%) for 2010–2012, 12 per 1, 000 patient days (1.2%) for 2013–2015, and 10 per 920 patient days (1.1%) for 2016–2018. Logistic regression revealed that significant predictor variables for PI were age, mechanical ventilation time, and preoperative Braden Scale score. The mean time to PI was 23 days after admission and over 14 days after surgery, indicating a low rate of intraoperative and ICU-associated PI. CONCLUSIONS: The incidence of PI was lower than anticipated given historic rates. Potential mechanisms by which these patients were protected from PI are discussed. Prospective studies to further investigate significant risk factors and effective prevention measures are warranted.